Risiko Produksi dan Pendapatan Usahatani Kakao di Desa Kuajang Binuang Kabupaten Polewali Mandar - Arsyad, Wahyuni; Mardiyati, Sri; Nadir, Nadir; Nailah, Nailah; Molla, Soleh (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2022)
Cocoa is a commodity that has high economic value and has the potential for sustainability to continue to be developed.  Cocoa is a mainstay commodity in various regions in Indonesia, one of which is West Sulawesi which is included in the five largest cocoa bean producing provinces in Indonesia.  This study aims to determine the level of production and income as well as the risk of production and income of cocoa farming in Kuajang Village, Binuang District, Polewali Mandar Regency. The method used in this study is a quantitative approach that emphasizes the analysis of numerical data.  The sampling technique was carried out using the simple random sampling method. The sample in this study was 40 cocoa farmer respondents or 20% of the cocoa farmer population, which totaled 200 people. Data was collected by observation, interviews and documentation.  Analysis of the data used is the Coefficient of Variation (CV) analysis.  The results showed that the CV value of production risk was 0,76 which was classified as high risk or very risky.  This is because of the attack of pests and plant diseases that reduce the production of cocoa plants.  While the CV value of income risk is 0,18 which is classified as low risk.  This risk also includes the impact of pests and diseases that cause low production and quality of cocoa beans.